NIKAH MUDA DALAM PANDANGAN MASYARAKAT DESA KEPULAUAN SIMEULUE (Studi Kasus di Desa Lubuk Baik, Kec. Alafan, Simeulue, Aceh) - Zamzami, Zamzami; Saputri, Mimi Wita; Alfairusy, Muhajir; Masrizal, Masrizal; Sartika, Diana Dewi (Master Program in Sociology, Faculty of Social and Political Sciences, Universitas Sriwijay, 2023)
Young marriage, in the view of the Simeulue community, is a new fact that is present today in a society that aims to avoid violence among teenagers. Young marriage is a sacred bond performed by a pair of teenage men and women who should not be married yet. The purpose of this study is to explain the views of the Simeulue community about the factors that influence the rise of young marriage and the social impact of young marriage. This research uses qualitative methods with data collection techniques through observation, interviews, and documentation. The results showed that the factors that influence parents to allow children to marry young are economic factors and environmental factors. Meanwhile, the impact that occurs due to young marriage is the disconnection of children's education and the family's economic conditions that are far from sufficient to meet family needs and cause disharmonious households, even divorce.